2021
DOI: 10.36474/caring.v5i2.202
|View full text |Cite
|
Sign up to set email alerts
|

Penatalaksanaan Perdarahan Postpartum di Negara Berkembang

Abstract: Latar Belakang: Kematian berhubungan dengan kehamilan, persalinan ataupun masa nifas. Upaya yang dilakukan dalam menurunkan angka kematian ibu tidak hanya diketahui dari tingginya cakupan, akan tetapi dapat diketahui dari kualitas pelayanan yang lebih menekankan pada kebutuhan kompetensi tenaga kesehatan, kelengkapan obat, peralatan, sarana dan prasarana disemua layanan kesehatan. Berdasarkan organisasi kesehatan dunia menytakan bahwa terjadinya kematian maternal tiap tahun 140.000 atau 1 wanita tiap 4 menit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Some efforts have been made by the Health Ministry to manage and improve the treatment of postpartum bleeding. 15 This study showed that 82.0% of mothers underwent standard delivery and 16.68% were by cesarean section, meaning that mothers with labor bleeding can still be attempted to deliver typically. Table 3 shows that bleeding has the potential for delivery with cesarean section approximately two times.…”
Section: Resultsmentioning
confidence: 80%
“…Some efforts have been made by the Health Ministry to manage and improve the treatment of postpartum bleeding. 15 This study showed that 82.0% of mothers underwent standard delivery and 16.68% were by cesarean section, meaning that mothers with labor bleeding can still be attempted to deliver typically. Table 3 shows that bleeding has the potential for delivery with cesarean section approximately two times.…”
Section: Resultsmentioning
confidence: 80%
“…Dari jumlah ini diperkirakan, sekitar 90% terjadi di Asia dan Afrika Sub-Sahara, 10% di negara berkembang lainnya dan kurang dari 1% terjadi di negara maju. Risiko kematian ibu lebih tinggi dari 1 dalam 10 kehamilan di negara berkembang, sedangkan di negara maju kurang dari 1 dalam 6.000 [2], [3].…”
Section: Pendahuluanunclassified
“…1 Nearly a quarter of all maternal deaths worldwide occur after childbirth, with postpartum hemorrhage being the leading cause in lowincome nations like Indonesia. [2][3][4] Postpartum hemorrhages are defined as blood losses of at least 500 mL and more than 1000 mL after vaginal and cesarean deliveries respectively. 5 The WHO's current recommendation for preventing postpartum hemorrhage involves aggressively managing the third stage of labor.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that uterine contractions can commence in less than two minutes after the initial carbetocin dose and persist for up to two hours. 2,7,8 To date, only a limited number of meta-analyses and systematic reviews have addressed the role of carbetocin, a long-acting oxytocin agonist, in preventing postpartum hemorrhage. Therefore, further investigation is necessary to elucidate the role of carbetocin in reducing postpartum bleeding.…”
Section: Introductionmentioning
confidence: 99%